2016
DOI: 10.1063/1.4965986
|View full text |Cite
|
Sign up to set email alerts
|

Single-dot spectroscopy of boron and phosphorus codoped silicon quantum dots

Abstract: Boron (B) and phosphorous (P) codoped silicon quantum dots (Si QDs) are dispersible in polar solvents without organic ligands, and exhibit size controllable photoluminescence (PL) from 0.85 to 1.85 eV due to the electronic transitions between the donor and the acceptor states. We study the PL spectra of the codoped Si QDs at room temperature and at 77 K. We show that the broad PL band of codoped colloidal Si QDs (full width at half maximum is over 400 meV) is composed of narrower PL bands of individual QDs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…The presence of these donor and acceptor states lowers the energy gap from 2.59 eV, for the undoped Si‐NC, to 1.82 eV, for the co‐doped one. In large Si‐NCs, by engineering impurity location, co‐doping can be exploited to tune the energy of the gap from the visible range to values below the energy gap of the Si‐bulk, in agreement wth the experimental observations . Moreover, very recently Hori et al have demonstrated using photoemission yield spectroscopy and photoluminescence spectroscopy that for B and P codoped Si‐NCs with relatively large sizes both the HOMO and LUMO levels are within the band gap of bulk Si crystal, confirming that these are acceptor and donor levels, and that, with decreasing the size from 9 to 1 nm, the HOMO level becomes about 0.46 eV deep and the LUMO level about 0.47 eV shallow, in fair agreement with the theoretical outcomes …”
Section: Co‐dopingsupporting
confidence: 64%
See 1 more Smart Citation
“…The presence of these donor and acceptor states lowers the energy gap from 2.59 eV, for the undoped Si‐NC, to 1.82 eV, for the co‐doped one. In large Si‐NCs, by engineering impurity location, co‐doping can be exploited to tune the energy of the gap from the visible range to values below the energy gap of the Si‐bulk, in agreement wth the experimental observations . Moreover, very recently Hori et al have demonstrated using photoemission yield spectroscopy and photoluminescence spectroscopy that for B and P codoped Si‐NCs with relatively large sizes both the HOMO and LUMO levels are within the band gap of bulk Si crystal, confirming that these are acceptor and donor levels, and that, with decreasing the size from 9 to 1 nm, the HOMO level becomes about 0.46 eV deep and the LUMO level about 0.47 eV shallow, in fair agreement with the theoretical outcomes …”
Section: Co‐dopingsupporting
confidence: 64%
“…It has, however, been shown that this quenching can be avoided when the Si‐NCs are simultaneously doped and compensated with B and P impurities. The co‐doped Si‐NCs exhibit PL energies red‐shifted with respect to those of the corresponding undoped Si‐NCs, moreover these energies can range from the visible to below the bandgap energy of the bulk Si . Thus, we will report here the outcomes of a systematic study of the structural, electronic and optical properties of B and P simultaneously doped Si‐NCs using ab initio DFT calculations .…”
Section: Co‐dopingmentioning
confidence: 99%
“…The very large difference of the fwhms indicates that there are some additional mechanisms to broaden the PL band in codoped Si QDs. As can be seen in Figure 3g, the fwhm of size-selected codoped Si QDs samples is larger than that of single codoped Si QDs (225 ± 40 meV) 40 (filled magenta square), despite the very small size distribution. This is another evidence of the existence of additional broadening mechanisms.…”
mentioning
confidence: 90%
“…Doped Si-NCs with diameter down to 3 nm have been synthetized using different strategies [89,90,110,111,112,113]. Among all, Fujii and coworkers developed an efficient procedure [114,115,116,117,118,119,120] where Si, SiO 2 , P 2 O 5 or B 2 O 3 were simultaneously sputter-deposited and then annealed in N 2 gas atmosphere. During annealing the B-or P-doped Si-NCs were grown in borosilicate (BSG) or phosphosilicate (PSG), i. e. B-or P-doped silica, glass matrices.…”
Section: Free-standing Nanocrystalsmentioning
confidence: 99%
“…More recently the same group reported a new method to obtain B and P codoped colloidal Si-NCs, where NCs were dispersed in methanol without a surface functionalization process [115,116,117,119]. To isolate Si-NCs from BPSG matrices, the BPSG films were dissolved in HF solution in ultrasonic bath.…”
Section: Codopingmentioning
confidence: 99%